KEPATUHAN DIET DAN STATUS TEKANAN DARAH PENDERITA HIPERTENSI PADA SAAT PUASA RAMADHAN - Diva Rachmawati; Mohammad Jaelani; Enny Rahmawati; Yulianto Yulianto (Poltekkes Kemenkes Semarang, 2019)
Background: Hypertension during Ramadan fasting can be due to metabolic processes in the body running more slowly, causing fat accumulation in the body. This condition will cause blood flow to be not smooth so the body needs more pressure so that blood carrying oxygen can get to the organs of the body immediately. Poor adherence to the diet during fasting will aggravate the condition of the body's ability to control blood pressure.Objective: To know diet compliance and blood pressure status of hypertension prolanis participants when doing fasting on Ramadhan month at Tlogosari Kulon Public Health Center.Method: This research was a descriptive study in the field of clinical nutrition with a cross sectional approach. The sample of the study was active prolanis hypertension participants at Tlogosari Kulon Kulon Health Center with 17 samples were taken using the total sampling method. Retrieving data on the level of knowledge using knowledge level form, intake and consumption pattern data using recall 1x24 hour form and FFQ form, blood pressure data using the patient’s medical record data during measurement in prolanis event.Results: Research subjects during Ramadan fasting showed as many as 13 people (76.5%) did not adhere to a diet and 7 people (43.2%) had uncontrolled blood pressure status.Conclusion: Poor adherence to the diet during Ramadhan fasting does not indicate a tendency towards uncontrolled blood pressure status.